2018
DOI: 10.15835/nbha46110788
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Traits Defining Breeding Criteria for Coastal Quinoa in Chile

Abstract: Coastal/lowland quinoa ecotype is an important source of germplasm due to its cultivation in cold-temperate and high latitude areas. However, the interaction of its morphological traits and yields to define breeding criteria is unknown. The present study was designed to characterize the phenotypic diversity of twelve coastal/lowland quinoas using sixteen standardized morphological descriptors under rainfed conditions in central Chile. Complementary analysis of uni-and multivariate tools allowed a fuller unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
(15 reference statements)
4
8
1
Order By: Relevance
“…High significant positive correlation values between inflorescence length and seed yield have also been observed in plants like barnyard grass (Norris, 1992), sorghum (Kenga et al, 2006) and perennial ryegrass (Abel et al, 2017). Likewise, significant positive association between seed yield and stem diameter as obtained in the present study has also been observed in other economically important plants like maize (Ali et al, 2017), wheat (Okuyama et al, 2005) and quinoa (Bhargava et al, 2008;Madrid et al, 2018). Thus, IL, SD and PW should be given proper attention in selection programmes for increasing grain yield in quinoa.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…High significant positive correlation values between inflorescence length and seed yield have also been observed in plants like barnyard grass (Norris, 1992), sorghum (Kenga et al, 2006) and perennial ryegrass (Abel et al, 2017). Likewise, significant positive association between seed yield and stem diameter as obtained in the present study has also been observed in other economically important plants like maize (Ali et al, 2017), wheat (Okuyama et al, 2005) and quinoa (Bhargava et al, 2008;Madrid et al, 2018). Thus, IL, SD and PW should be given proper attention in selection programmes for increasing grain yield in quinoa.…”
Section: Resultssupporting
confidence: 82%
“…Genetic gain, a product of heritability and selection differential, has been frequently used as a guiding factor in selection programmes in a number of plants (Badigannavar and Ganapathi, 2018;Kumar and Das, 2018;Mishra et al, 2015) including quinoa (Bhargava et al, 2007(Bhargava et al, , 2008Madrid et al, 2018). After two selection cycles, the results demonstrated that the red line presented a positive genetic gain (p ≤ 0.05) for the PH and NB variables and a negative genetic gain for IW, IL, GD and SC (Tab.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed a significant correlation between AP and DT for all populations, as also been observed by Spehar and Santos (2005) when evaluating the agronomic performance of selected quinoa and by Madrid et al (2018) in the evaluation of morphological characteristics related to the improvement of yield in quinoa. LP and DP were positively associated with AP in P1, P2 and P4, indicating that individuals with a greater height develop larger panicles, as found by Alanoca and Machaca (2017), Farooq et al (2018) and Morillo et al (2020).…”
Section: Resultssupporting
confidence: 75%
“…)), and coastal, in central and southern zone at sea level (34–43°S; <300 m a.s.l. ), with an estimated total area of 700 ha that is expected to continue increasing (Madrid et al ., 2018). While the world's largest quinoa production corresponds to the highlands ecotype, Chile's most produced genotypes belong to the coastal ecotype, so recent studies have focused on the improvement of their productivity and commercial value (Murphy et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%